Nutritional habits and nutritional status of students of higher education institutions of the medical educational field in the Republic of Serbia - Stojanović Svetlana T. (Association of Nurses Technicians and Midwives, 2017)
Students of higher education institutions in the medical education field should have a high educational level when it comes to proper nutrition, which is an important factor in the promotion and maintenance of good health. In this text, without a critical review, are presented the results of major numbers of researches which consider nutrition habits and nutrition categories of students of medical sciences of University of Belgrade, Novi Sad, Kragujevac and Nis as well as students of Higher Education School of Professional Health Studies in Belgrade, while for students of University in Pristina with temporary location in Kosovska Mitrovica are presented only results of nutrition habits researches. This kind of research can be useful not only to get a better view of the actual situation, but also in summering educational and prevential programmes and also for creating educational programme contents.